2021
DOI: 10.1001/jamainternmed.2021.1793
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Vaping Cessation Text Message Program Among Young Adult e-Cigarette Users

Abstract: IMPORTANCE e-Cigarettes are the most commonly used tobacco product among young adults (YAs). Despite the harms of nicotine exposure among YAs, there are few, if any, empirically tested vaping cessation interventions available.OBJECTIVE To determine the effectiveness of a text message program for vaping cessation among YAs vs assessment-only control. DESIGN, SETTING, AND PARTICIPANTSA parallel, 2-group, double-blind, individually randomized clinical trial was conducted from December 2019 to November 2020 among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 41 publications
2
102
0
Order By: Relevance
“…This program offers young people a minimum of 4 weeks of messages tailored to age and a resettable quit date, which are focused on skills and confidence building [ 37 ]. Results from a randomized control trial revealed that this program achieved 30-day point prevalence abstinence of 24.1% at 7 months compared with the control (18.6%) [ 12 ], adding support to our findings in relation to the value of personalization and positive-message framing. Our findings also suggest that there is an appeal among users for gamification and behavioral self-monitoring when it comes to e-cigarette interventions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This program offers young people a minimum of 4 weeks of messages tailored to age and a resettable quit date, which are focused on skills and confidence building [ 37 ]. Results from a randomized control trial revealed that this program achieved 30-day point prevalence abstinence of 24.1% at 7 months compared with the control (18.6%) [ 12 ], adding support to our findings in relation to the value of personalization and positive-message framing. Our findings also suggest that there is an appeal among users for gamification and behavioral self-monitoring when it comes to e-cigarette interventions.…”
Section: Discussionsupporting
confidence: 81%
“…Given the popularity of smartphones among young adults [ 10 ], a few mobile-based interventions are now on the market. One of them includes an SMS text messaging intervention to promote e-cigarette cessation among young adults [ 11 ], for which preliminary evidence in relation to user engagement and effectiveness is promising [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pilot trial showed promise for nicotine replacement therapy, tapering use, and self-guided methods for e-cigarette cessation among young adults ( 26 ). A randomized clinical trial among more than 2,000 young adult e-cigarette users found better cessation rates in a text-messaging program (24.1%) than in an assessment-only control condition after 7 months (18.6%) ( 27 ). The cessation program, This is Quitting, used a combination of social support and cognitive and behavioral coping skills training conducted entirely through text messages ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial among more than 2,000 young adult e-cigarette users found better cessation rates in a text-messaging program (24.1%) than in an assessment-only control condition after 7 months (18.6%) ( 27 ). The cessation program, This is Quitting, used a combination of social support and cognitive and behavioral coping skills training conducted entirely through text messages ( 27 ). Among our sample, those who attempted to quit primarily did it “cold turkey” and almost half of those who attempted reported that cessation lasted less than a month.…”
Section: Discussionmentioning
confidence: 99%
“…These studies did not mention shared decision making; however, similar concepts and strategies could be taken into consideration. Two studies regarding adolescent smoking cessation using text message and smartphone apps showed a positive effect and a cessation rate of 31% using an interactive, supportive, self-motivating design, which are important features [18,19]. A recent systematic review highlighted the principles and effectiveness of multiple behavioral interventions and personalized counseling, which are also important in our SDM model [17].…”
Section: Introductionmentioning
confidence: 99%